Direct synthesis of bimetallic PtCo mesoporous nanospheres as efficient bifunctional electrocatalysts for both oxygen reduction reaction and methanol oxidation reaction. (2nd March 2018) - Wang, Hongjing; Yu, Hongjie; Li, Yinghao; Yin, Shuli; Xue, Hairong; Li, Xiaonian; Xu, You; Wang, Liang
Abstract: The engineering of electrocatalysts with high performance for cathodic and/or anodic catalytic reactions is of great urgency for the development of direct methanol fuel cells. Pt-based bimetallic alloys have recently received considerable attention in the field of fuel cells because of their superior catalytic performance towards both fuel molecule electro-oxidation and oxygen reduction. In this work, bimetallic PtCo mesoporous nanospheres (PtCo MNs) with uniform size and morphology have been prepared by a one-step method with a high yield. The as-made PtCo MNs show superior catalytic activities for both oxygen reduction reaction and methanol oxidation reaction relative to Pt MNs and commercial Pt/C catalyst, attributed to their mesoporous structure and bimetallic composition.